2016
DOI: 10.1080/17470218.2015.1054294
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between prospective memory and episodic future thinking in younger and older adulthood

Abstract: Episodic future thinking (EFT), the ability to project into the future to "preexperience" an event, and prospective memory (PM), remembering to perform an intended action, are both examples of future-oriented cognition. Recently it has been suggested that EFT might contribute to PM performance but to date few studies have examined the relationship between these two capacities. The aim of the present study was to investigate the nature and specificity of this relationship, as well as whether it varies with age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 52 publications
(86 reference statements)
4
36
0
Order By: Relevance
“…These beneficial effects were of similar magnitude in older and younger adults despite the existence of episodic future thinking deficits in older adults (89), but were reduced in heavy social drinkers, who also show episodic simulation deficits (91). Overall these findings both highlight a functional benefit of episodic future thinking for prospective memory and also suggest a link between the two forms of prospection, which is further supported by a study that revealed significant positive correlations between episodic future thinking and prospective memory abilities in both young and old adults (19). …”
Section: Functions Of Episodic Future Thinkingsupporting
confidence: 65%
“…These beneficial effects were of similar magnitude in older and younger adults despite the existence of episodic future thinking deficits in older adults (89), but were reduced in heavy social drinkers, who also show episodic simulation deficits (91). Overall these findings both highlight a functional benefit of episodic future thinking for prospective memory and also suggest a link between the two forms of prospection, which is further supported by a study that revealed significant positive correlations between episodic future thinking and prospective memory abilities in both young and old adults (19). …”
Section: Functions Of Episodic Future Thinkingsupporting
confidence: 65%
“…In addition, Brewer and Marsh (2010) demonstrated that familiarity with the context of the ongoing task improved people's performance on a prospective memory task because it allowed them to better encode their future plan. Finally, there is some evidence that prospective memory and EFT draw on similar cognitive processes (Terrett et al, 2016). In the current experiments, it is reasonable to assume that the majority of participants were familiar with the context of a shopping mall and, therefore, would be able to plan ahead while encoding the prospective memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the hypothesized preparatory function of future thinking has been demonstrated in the context of planning and problem solving (e.g., Arnold, Iaria, & Ekstron, 2016; Gerlach, Spreng, Gilmore, & Schacter, 2011; Spreng, Stevens, Chamberlain, Gilmore & Schacter, 2010), prospective memory (e.g., Terrett et al, 2016), decision-making (e.g., Benoit, Gilbert, & Burgess, 2011; Peters & Büchel, 2010), and emotion regulation (e.g., Taylor, Pham, Rivkin, & Armor, 1998; for review, see Schacter, 2012). However, despite Ingvar’s initial emphasis on the importance of constructing alternative behavior patterns, there remains very little investigation of the actual simulation of alternative versions of future events.…”
Section: Introductionmentioning
confidence: 99%